Answer :

(i)

Given:

We first put x = 0 in the expression and obtain:

⇒ 9/21 = -5/3 which does not hold true.

∴ x=0 is not a solution.

Now, let ……………… (1)

Multiply numerator and denominator of second expression by 4x:

……………….(2)

∴ From equation (1) and (2), we get:

Cross multiply and obtain:

⇒ 28x – 35 = 6x + 9

⇒ 28x – 6x = 9 + 35

⇒ 22x = 44

⇒ x = 44/22

⇒ x = 2

∴ x=2 is the solution.

(ii)

Given:

We first put y = 0 in the expression and obtain:

⇒ (-12)/(-4) = 8/1 which does not hold true.

∴ y=0 is not a solution.

Now, let ……………… (1)

Multiply numerator and denominator of second expression by 5y:

……………….(2)

∴ From equation (1) and (2), we get:

Cross multiply and obtain:

⇒ y + 8 = 3 + 6y

⇒ 6y – y = 8 - 3

⇒ 5y = 5

⇒ y = 1

∴ y=1 is the solution.

Rate this question :

Check whether theMHB - Math Part-I

Convert the folloMHB - Math Part-I

a, b ,c are in coMHB - Math Part-I

If <span lang="ENMHB - Math Part-I

5m-n=3m+4n, then MHB - Math Part-I

Fill in the blankMHB - Math Part-I

Which number shouMHB - Math Part-I

Solve the followiMHB - Math Part-I

Solve the followiMHB - Math Part-I